Wozu Führung - Dimensionen einer Kunst - Dellbrügger, Peter [Hrsg.] (KIT Scientific Publishing, 2013)
To understand leadership as an art is the objective of this book. One key aspect is the topic of freedom: Stefan Brotbeck develops a phenomenology of "Unfreiheit" by unmasking mechanisms which he describes as social denaturation. Further topics are amongst others the "liberation" of leadership (Rehn), Hierarchie (Hardorp), confidence (Lavecchia), education (Dietz) and sense-making (Werner).